Output Regulation for Saturated Systems with Nonlinear Exosystem - Huang Wei (Institute of Advanced Engineering and Science, 2014)
In this brief, we investigate the output regulation problem of saturated linear system under the action of nonlinear exosystem. Particularly, for saturated systems with periodically time-dependent exosytem, the K-step asymptotically regulatable region is given, which is a set of all initial states of the plant and the ecosystem. Improved internal model principles are constructed and the feedback controller is designed to ensure exponential output regulation in the regulatable region with disturbance rejection. Simulation examples are given to illustrate the effectiveness of proposed method, the systems go into stable rapidly and periodically.DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5535